O acordo de compartilhamento de risco como instrumento de desenvolvimento da indústria farmacêutica - Miranda, Ciro Carvalho (2024)
The exercise of the economic activity of producing medicines, while not an exclusive State function, was granted to the private sector by the 1988 Federal Constitution, despite being considered an activity of public interest. Considering the constitutional authorization granted to the State to also operate in this field, contributing to technological development and innovation aimed at the proper functioning of the Unified Health System, the activity of promoting the pharmaceutical production activity in conjunction with the private sector is shown to be viable. The State's role in the pharmaceutical market should also focus on overcoming Brazil's lack of autonomy with imports of finished products or inputs, indispensable for domestic production, which leads to a trade deficit and fragility of national sovereignty. In this context, in situations of analysis for the incorporation of a drug into the Unified Health System that has a high price and whose disease has a low prevalence in the population, considering the possible existence of uncertainty regarding its efficacy, the Risk Sharing Agreement proves to be a legally viable instrument to, at the same time that it enables the use of the drug in real-world conditions to obtain reliable data, link the payment by the public power to the effective performance of the pharmaceutical substance. In this context, this thesis aims to evaluate the adoption of the Risk Sharing Agreement as a valid instrument to, in the process of incorporating drugs into the Unified Health System, contribute to the promotion of the national industry. To this end, the hypothetical-deductive method is used, with the aid of bibliographic research as a methodological procedure. As conclusions, it is found that: 1) The Risk Sharing Agreement has applicability as an instrument to overcome uncertainties related to the efficacy of the drug, in which payment will be made based on performance; 2) The Risk Sharing Agreement is a low-scale and high-complexity instrument, not indicated for routine use, given the implementation cost; 3) For the Risk Sharing Agreement to be an instrument that also enables innovation and technological development of the national pharmaceutical industry, there must be an improvement of Bill 667/2021 and the selection, on a case-by-case basis, of the modality to be adopted.